THE INFLUENCE OF MANURE AND DOLOMIT ON THE GROWTH AND PRODUCTION OF LONG BEANS (Vigna sinensis L.) - Thomas Wagin; Oktavianus Lumban Tobing; Nur Rochman (JURNAL AGRONIDA, 2017)
This study was aimed to determine the effect of dosage of  cow manure and, dolomite on the growth and production of long  beans. This research was conducted in experimental field of Agroteknologi Department of Djuanda University Bogor. The study was prepared according to Completely Randomized Design (RAL), factorial. The first factor was the dose of cow manure according to recommendation consisting of 4 levels: 0R, 0.5 R, 1R, and 1.5R . The second factor is the recommended dolomite consisting of 4 levels: 0R, 0.5 R, 1R, and 1.5 R.  The results showed that the average height of the plant at age 6 MST, the number of leaves 4 MST and 6 MST, the number of flowers and the amount of fruit 6 MST, wet fruit weight of 3rd fruit harvest, dry weight of stem aged 8 MST influenced by cow manure.  While plant 4 MST, number of leaves 4,6 and 8 MST, number of branches 4, 6 and 8 MST, 6.8 MST of flowers and number of fruit 6,8 MST, weight lenghtof fruit harvest to-1, wet fruit weight of whole harvest 1st, dry weight of 3rd harvest, wet weight of stem, dry weight of stem, wet weight of root influenced by dolomite.Keywords: Long beans, plant height, the amount of fruit, fruit weight